Polyaniline/Graphene-Based Electrochemical Biosensor for Sensitive Detection of Glucose - Ge, Yuqing; Chen, Zhihua; Jin, Qinghui; Mao, Hongju; Liu, Jianshe; Zhao, Jianlong (Asian Journal of Chemistry, 2013)
A novel approach for glucose biosensor fabrication was described. It based on immobilization of glucose oxidase on polyaniline/graphene composite membrane modified glassy carbon electrode. Cyclic voltammetry demonstrated that modified electrodes owned good electrochemical activity, superior sensitivity and high stability. The good electrocatalytical activity toward H2O2 and O2 might be attributed to the synergistic effect of graphene and polyaniline. The results showed that the electrochemical biosensor had a wide linear response from 0.1 to 10 mM.